Advantages and limitations of community-based post-disaster housing reconstruction projects. Issue 4 (12th September 2016) - Ophiyandri, Taufika; Amaratunga, Dilanthi; Keraminiyage, Kaushal
Abstract : Purpose: The purpose of this paper is to discuss the advantages and limitations of the implementation of a community-based method in post-disaster housing reconstruction. Design/methodology/approach: The research was based on multiple case studies in the implementation of a community-based post-disaster housing reconstruction project (CPHRP) in Indonesia. Data were gathered by conducting semi-structured interviews and a questionnaire survey. Findings: The research reveals 22 advantages of a CPHRP. Four advantages can be categorised as highly significant. They are create sense of ownership, fit to local culture/customs/wisdom, build beneficiaries' confidence and minimize corruption. There are some advantages that cannot be delivered if the housing reconstruction is conducted using a contractor-based approach. It was also found that psychological advantages are more dominant than the physical advantages. Despite its numerous advantages, CPHRP has limitations. First, it requires a long pre-construction process and, second, there is a limitation with regard to the capacity of implementer and there are limitations within the community itself. Originality/value: This paper is very specific because it attempts to discover the advantages and limitations of a CPHRP.